2015
DOI: 10.1021/acs.langmuir.5b00139
|View full text |Cite
|
Sign up to set email alerts
|

Gated Mesoporous Silica Nanoparticles for the Controlled Delivery of Drugs in Cancer Cells

Abstract: In recent years, mesoporous silica nanoparticles (MSNs) have been used as effective supports for the development of controlled-release nanodevices that are able to act as multifunctional delivery platforms for the encapsulation of therapeutic agents, enhancing their bioavailability and overcoming common issues such as poor water solubility and poor stability of some drugs. In particular, redox-responsive delivery systems have attracted the attention of scientists because of the intracellular reductive environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 63 publications
2
75
0
1
Order By: Relevance
“…To establish redox-responsive DDS, disulfide bonds were absolutely necessary, and the gatekeepers may vary, but mainly based on nanoparticles, 44,45,78,79 supramolecule or biomacromolecule, [80][81][82][83][84][85][86][87][88] and polymers. [89][90][91][92][93][94] Many inorganic nanoparticles have been used as nanovalves to seal the drug molecule into the channels of MSN through covalently functionalizing MSN with disulfide containing linkers, such as CdS, 44 Fe 3 O 4 , 45 gold, 78 and ZnO. 79 Giri et al 45 synthesized a controlled-release delivery system that was based on MCM-41-type MSN capped with superparamagnetic Fe 3 O 4 nanoparticles through disulfide bonds and was stimuli-responsive and chemically inert to guest molecules entrapped in the matrix.…”
Section: Redox-responsive Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…To establish redox-responsive DDS, disulfide bonds were absolutely necessary, and the gatekeepers may vary, but mainly based on nanoparticles, 44,45,78,79 supramolecule or biomacromolecule, [80][81][82][83][84][85][86][87][88] and polymers. [89][90][91][92][93][94] Many inorganic nanoparticles have been used as nanovalves to seal the drug molecule into the channels of MSN through covalently functionalizing MSN with disulfide containing linkers, such as CdS, 44 Fe 3 O 4 , 45 gold, 78 and ZnO. 79 Giri et al 45 synthesized a controlled-release delivery system that was based on MCM-41-type MSN capped with superparamagnetic Fe 3 O 4 nanoparticles through disulfide bonds and was stimuli-responsive and chemically inert to guest molecules entrapped in the matrix.…”
Section: Redox-responsive Drug Deliverymentioning
confidence: 99%
“…Other reports using PEG as gatekeepers also showed similar results. [90][91][92] Liu et al 95 reported a redox-responsive DDS by using crosslinked poly N-acryloxysuccinimide as a gatekeeper. Poly N-acryloxysuccinimide was anchored to the outlet of silica mesopore through reversible addition-fragmentation chain transfer polymerization.…”
mentioning
confidence: 99%
“…By integrating a GSH stimulus‐responsive segment into a nanoparticle system, the release profiles of the drugs can be fine‐tuned. For example, −S−S− linkages are stable in blood plasma, but they are cleaved at elevated redox potentials . In addition, the low pH microenvironment of cancer tissues is typically useful in the development of stimulus‐responsive therapeutic agents .…”
Section: Introductionmentioning
confidence: 99%
“…Reduction-sensitive systems can also be adopted in nanocarriers, such as cationic polyamidoamine dendrimers, dendrimer-encapsulated gold nanoparticles, 36 disulfide crosslink nanogels, 37 liposomes, 38 capped mesoporous nanoparticles, 39 etc. For liposome-based systems, they usually have two forms of disulfide-conjugated lipids on their surface.…”
Section: Reduction-responsive Systemsmentioning
confidence: 99%